CURRICULUM, LEARNING STRATEGIES, AND EVALUATION ACCORDING TO ISLAM - Putri, Yulita; Nurhuda, Abid; Huda, Ali Anhar Syi’bul (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Education is a way to plan for the future of mankind which consists of many components including curriculum, strategy, and evaluation. These three things form an interrelated system such as a guide in life. Islam as a comprehensive religion will certainly not be separated from discussing the guidelines of the education system in its legal sources, namely the Al-Qur'an, Assunnah, and Ijma'. And the purpose of this study is to describe the Curriculum, Learning Strategies, and Evaluation According to Islam. The method used is qualitative with a literature study approach. The results of the study show that the curriculum is a systematic Manhaj to achieve the goals of Islamic education. The learning strategy is considered the outline of the course that must be followed in the learning process and is likened to the main points, namely faith, and Islam. While evaluation is often seen as an exercise to find out the extent of a student's abilities and how many results he can get from various activities so that later improvements or enrichment will emerge.